Children in Digital Age – Czech Perspective - Westphalová, Lenka (Children in Digital Age, 2025)
Abstract:This paper discusses the various rights of children that may be affected in cyberspace. These are the right to privacy, the right to self-determination, and the protection of personal data. It also seeks to contribute to the debate on the notion of digital adulthood (self-legitimacy). The issue of the child versus the Internet is nowadays vast and wide-ranging; it affects several levels, from criminal sanctions to the private law exercise of parental responsibility and the enabling of self-determination of the child or the protection of the child as a consumer. It also ranges from the proper legal context such as the provision of teaching in schools to systematic solutions at the ministerial level. Keywords: cyberspace, child rights, privacy, data protection, digital adulthood